Investigation of xy ratio in different tissues of an intersex goat chimera - Klecska, Eszter; Biró, Bálint; Egerszegi, István; Fábián, Renáta; Hiripi, László; Oláh, János; Kovács, András; Bodó, Szilárd (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
Many forms of chimerism in mammals are known. Chimeras are made up of cells of different origins. In life science, chimeric models are important (eg. stem cells, xenotransplantation). The most common background of chimerism in the Bovidae family is freemartinism, which develops during different sex gestations. At different stages of embryonic development, the fetal vasculatures form anastomoses in the placenta, allowing the twins’ blood to mix, which results in the exchange of hormones and some hematopoietic cells. This can lead to female infertility. The goat chimera of this study was born from twin gestation and showed genotype XX-XY (52-48%) in the blood cell assay. Our goal was to determine the ratio of sex chromosomes in 13 tissue types. This was detected by PCR using a fluorescent labeled primer designed for AMEL gene. Fragment analysis followed by AUC ratio matching gives the ratio of sex chromosomes in various tissues. We found that this ratio is different in the studied tissues. Afterwards, AMEL fragments were cloned and sequenced. Sequence alignment revealed the deletion of AMEL-Y gene.